Evaluation of antioxidant, antiinflammatory, and gastroprotective properties of Rubus fruticosus L. fruit juice. (15th April 2018) - Monforte, Maria Teresa; Smeriglio, Antonella; Germanò, Maria Paola; Pergolizzi, Simona; Circosta, Clara; Galati, Enza Maria
Abstract : The juice of R. fruticosus (RFJ) fruits grown in Sicily was analysed for polyphenol compounds and tested to evaluate in vitro antioxidant and in vivo antiinflammatory and gastroprotective effects. RFJ, containing mainly anthocyanins, such as cyanidin derivatives, significant amounts of phenolic acids, and smaller amounts of flavonoids, showed significant antioxidant activity in DPPH (2, 2‐diphenyl‐1‐picrylhydrazyl radical) (4, 147.194 ± 17.199 mg trolox equivalent [TE]/100 ml), TE antioxidant capacity (8, 312.444 ± 43.055 mg TE/100 ml), ferric reducing antioxidant power (2, 177.830 ± 21.015 mg TE/100 ml), oxygen radical absorbance capacity (95, 377.674 ± 616.194 μmol TE/100 ml juice), and β‐carotene bleaching (72% ± 4.58) assay. In vivo studies showed that RFJ inhibit significantly the carrageenan‐induced paw oedema (63–71%) in rats and possess antiinflammatory effects particularly significant in association with phenylbutazone (94–96%). In addition, RFJ pretreatment was able to prevent the ethanol‐induced ulcerogenic effect in rats. All in vivo results were corroborated by histopathological observations and are in good agreement with antioxidant activity, confirming the relationships between biological effects observed and radical scavenging properties of RFJ.